Implementation and evaluation of hybrid broadcasting system for webcasts. (2018) - Ozaki, Takeshi; Gotoh, Yusuke
Due to the recent popularisation of grid environments, streaming delivery using broadcast and telecommunication method systems is attracting great attention. In streaming delivery in hybrid broadcasting environments, clients concurrently receive such streaming data as music or movies from both broadcasting and telecommunication systems. Although these systems compensate for their respective the demerits, the waiting time is lengthened if the system does not deliver the data efficiently. To reduce this waiting time, many researches have proposed scheduling methods. However, since most scheduling methods use a computer simulation, they do not clearly show their effectiveness. In this paper, we design and implement a hybrid broadcasting system to solve the problems of conventional methods. In our proposed system, we evaluate how efficiently they reduce waiting times using scheduling methods.